Perbedaan Kombinasi Konsentrasi Bahan Pengikat Pati Garut (Maranta Arundinaceae. L) Dan Pati Talas (Colocasia Esculanta L. Scoot) Terhadap Karakteristik Fisik Sediaan Tablet Hisap Ekstrak Jahe Merah (Zingiber Officinale Var. Rubrum) - Devi, Sisca; Baiti, Hilma Nur (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
Red ginger contains gingerol which is used as a throat lozenge. One of the dosage forms used in developing the use of red ginger is lozenges. Making lozenges requires additional ingredients in the form of a binder which can be obtained from starch. Arrowroot starch and taro starch contain amylose and amylopectin which have the ability to adhere. The combination of the use of arrowroot starch and taro starch binders has an impact on the characteristics of the lozenges produced. This research aims to determine the differences in the combination of using concentrations of binding agents, namely arrowroot starch and taro starch, on the physical characteristics of red ginger extract lozenges.This research is an experimental study with the independent variable being the combination of concentrations of arrowroot starch and taro starch (100:0); (50:50); (0:100). Testing of the physical characteristics of red ginger extract lozenges included organoleptic and tablet dimensions, weight uniformity, tablet hardness and friability and disintegration time. Analysis of normally distributed and homogeneous data using One-Way Anova at a confidence level of 95% followed by Post Hoc testing. The Kruskal-Wallis test is used for data that is not normally and homogeneously distributed followed by the Mann Whitney test.The test results showed that the combination of concentrations of arrowroot starch and taro starch binders had an effect on the physical characteristics, namely tablet hardness and brittleness and tablet disintegration time (p<0.05).